Concept And Theory Of Legal Subjects In Islamic Law - Ending Solehudin; Watni Marpaung (ISNU Sumatera Utara, 2024)
This study explores the concept and theory of legal subjects (mukallaf) in Islamic law, focusing on individuals deemed responsible for carrying out legal obligations (taklif). A mukallaf is defined as a person who is mature, rational, and free from hindrances such as coercion or ignorance, ensuring they understand and accept the responsibilities and rights imposed upon them by Islamic law. The dynamic nature of the mukallaf, shaped by time and place, highlights the importance of aligning legal rulings with the conditions of legal subjects. The research employs a juridical-normative approach, analyzing primary sources of Islamic law, such as the Qur’an, Hadith, and classical legal texts. This method focuses on examining the normative aspects of legal subjects and their evolving role within the framework of Islamic jurisprudence. Secondary data from scholarly works on Islamic law are also utilized to deepen the analysis of the mukallaf's criteria and responsibilities. The findings reveal that the legal obligations imposed on mukallaf must take into account their rational capacity, which influences their ability to fulfill taklif. Changes in societal context necessitate the continuous adaptation of legal rulings to ensure fairness and relevance. The study underscores that reason (aql) plays a central role in determining legal accountability, with the presence or absence of reason dictating the nature of the obligations imposed. In conclusion, the concept of mukallaf reflects a balanced relationship between law and its subjects, where the application of Islamic law must remain responsive to the evolving conditions of individuals while adhering to the principles of Sharia.